Suriname : Technical Assistance Report-External Sector Statistics. (IMF Staff Country Reports; Country Report, 2022)
A technical assistance (TA) mission on external sector statistics (ESS) was conducted in Paramaribo, Suriname, during March 2-13, 2020. The mission was part of the Caribbean Regional Technical Assistance Centre (CARTAC) work program on ESS and was carried out in response to a request from the Central Bank of Suriname (CBvS). The mission reviewed estimates and coverage of the balance of payments and international investment position (IIP), which have been prepared in the sixth edition of the Balance of Payments and International Investment Position Manual (BPM6) format. In particular, the mission's work mainly aimed at enhancing the coverage and the classification of (i) currency and deposits assets held abroad by the nonfinancial sector; (ii) insurance services, transport, travel account and trade credit and advances; (iii) offshore petroleum exploration companies; (iv) government external debt; and (iv) the use of business survey. Improvements in these key areas will facilitate a more robust assessment of external sector developments. Reliable ESS is essential for informed economic policy-making by the authorities and for IMF's surveillance.